Evaluation of the Italian version of the elderly mobility scale in older hospitalized patients - Nicolai, Moreno; Casoni, Elisa; Bertino, Emanuela; David, Letizia; Polverigiani, Chiara; Mallucci, Federica; Fioretti, Paola; Leonzi, Sara; Bevilacqua, Roberta; Barbarossa, Federico; Maranesi, Elvira; Baccini, Marco; et al. (Frontiers in Public Health, 2023)
Introduction: Reliable and valid assessment tools are needed to evaluate and predict physical function in older hospitalized patients. The aim of this study is to develop the Italian version of the Elderly Mobility Scale (I-EMS) and to evaluate its validity and inter-rater reliability for use with geriatric inpatients. Methods: The study consists of two phases: (i) translation, where EMS version 2 was translated into Italian by two teams, each comprising 2 bilingual physiotherapists; translations were back translated by 2 native English speakers, and a committee of 2 physiotherapists and 1 physician refined the initial I-EMS version, which was pilot-tested for clarity in a group of ten experienced geriatric physiotherapists; (ii) an observational study assessed I-EMS metrics (reliability, validity) in older Italian inpatients at IRCCS INRCA (Ancona, Italy) between September 2022 and April 2023. Results: No statistically significant differences were found between the scores of individual items and the total score assigned by different raters. The ICC for total I-EMS was 0.951, SEM was 1.10 and MDC95 was 3.06. The absolute agreement and weighted kappa for individual items ranged 80.32%-100% and 8.2-1, respectively. The validity of I-EMS was supported by a significant (p<0.05) correlation with the Barthel Index (r = 0.827 and 0.834 for the I-EMS administered by rater A and rater B, respectively). Conclusions: I-EMS showed good internal consistency and inter-rater reliability, and confirmed construct validity with respect to BI. Therefore, it can safely be used as an assessment tool for hospitalized Italian geriatric patients. Ethics: Approved by the IRCCS INRCA Hospital Ethic Committee (Ancona, Italy) (Process No. 43919/2021) and registered on ClinicalTrials.gov (Registration No. NCT05806242; 10 April 2022). Participants received written information and provided informed consent.